SPINEL PERIDOTITE XENOLITHS FROM THE TARIAT DEPRESSION, MONGOLIA. I: MAJOR ELEMENT CHEMISTRY AND MINERALOGY OF A PRIMITIVE MANTLE XENOLITH SUITE - Kovalenko V.I.; Preß S.; Wirr G.; Seck H.A.; Eonov D. (My University, 1986)
For mantle peridotite xenoliths from the Tariat Depression in central Mongolia an origin as partial melt residues has been inferred from the systematic change of bulk chemical compositions with mineral chemistries and modal compositions. The suite is dominated by primitive to slightly depleted lherzolites ranging from 15.7 to 7.9 wt.% of modal clinopyroxene, whereas harzburgites are rare. An increase of clinopyroxene to more than 20% in three samples is unrelated to liquid/crystal equilibria and is concluded to be the result of metamorphic differentiation. Leaving this enrichment of clinopyroxene aside, seven out of the twelve xenoliths studied come close to pyrolite in terms of mode and bulk chemistry. The primitive nature of these xenoliths is further emphazised by the low ratios of Cr/(Cr + Al + Fe) in their spinels, ranging from 0.075 to 0.087. In the majority of the samples studied orthopyroxene is chemically zoned with Al and Cr decreasing from core to rim. Temperatures of about 1050°C and about 950°C are derived for cores and rims, respectively. No zoning is observed for Ca in orthopyroxene and temperatures obtained from the solubility of CaO in orthopyroxene are close to 950°C, which shows that with respect to Ca the orthopyroxenes had already reequilibrated to the lower temperature. This and the zoning of Al and Cr may be related to cooling after some initial thermal perturbation or to cooling in a diapir.